Analysis of the possibilities of building the railway Rail Baltica in Lithuania - Jonaitis, Jonas; Butkevičius, Jonas (Transport, 2005)
The article deals with the objectives and possibilities of building the railway Rail Baltica through the Lithuanian territory, covers the alternatives of the choice of routes. In Lithuania's national transport policy the connection with Central and Western Europe by a direct, efficient and high‐quality railway link has high priority. A significant chain of building a new chain is a bypass of Kaunas, therefore the alternatives of a bypass around Kaunas are being analysed. The article also presents the choice of location and types of stations, an alternative version of the route. The location of the stations was studied together with all other aspects of the new line (alignment parameters, travelling time, environmental impact and investment cost). It is recommended to considerably analyse possibilities to build the Rail Baltica route through Vilnius with a possible branch‐line to Kaunas. Building of the route Rail Baltica is a technically complicated project, thus a focus is laid upon technical decisions.First Published Online: 27 Oct 2010